2011
DOI: 10.1186/1471-2458-11-s3-s24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breastfeeding promotion interventions on breastfeeding rates, with special focus on developing countries

Abstract: BackgroundGiven the recognized benefits of breastfeeding for the health of the mother and infants, the World Health Organization (WHO) recommends exclusive breastfeeding (EBF) for the first six months of life. However, the prevalence of EBF is low globally in many of the developing and developed countries around the world. There is much interest in the effectiveness of breastfeeding promotion interventions on breastfeeding rates in early infancy.MethodsA systematic literature was conducted to identify all stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
205
1
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(235 citation statements)
references
References 62 publications
14
205
1
15
Order By: Relevance
“…19 A meta-analysis of 53 studies, has demonstrated that prenatal and postnatal counseling increased EBF rates manifold. 20 We observed comparable literacy rates in both groups. A previous study concluded that a higher maternal educational level was observed to favor EBF significantly (p < 0.05) when compared to illiterate mothers.…”
Section: Discussionsupporting
confidence: 57%
“…19 A meta-analysis of 53 studies, has demonstrated that prenatal and postnatal counseling increased EBF rates manifold. 20 We observed comparable literacy rates in both groups. A previous study concluded that a higher maternal educational level was observed to favor EBF significantly (p < 0.05) when compared to illiterate mothers.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we have demonstrated that the rate of breastfeeding was significantly higher among patients who attended the childbirth preparedness course. Likewise, Imdad et al [27] reported that prenatal counseling had a significant impact on breastfeeding outcomes at 4-6 weeks [27].…”
Section: Discussionmentioning
confidence: 99%
“…When these interventions are performed in prenatal and puerperium, their effect is longer lasting, accruing benefits from breastfeeding up to six months of age (23)(24) . In view of this, it is evident that educational action is a strategy to promote breastfeeding; nevertheless, these programs are often carried out in a unidirectional form, without valorizing the woman as protagonist in this process, or her prior knowledge.…”
Section: Discussionmentioning
confidence: 99%